Dual Monoamine Oxidase and Cholinesterase Inhibitors with Different Heterocyclic Scaffolds - Gulcan, Hayrettin O.; Orhan, Ilkay E. (Bentham Science Publ Ltd, 2021)
For the last two decades, there has been research interest on the design of molecules possessing dual inhibitory potential on cholinesterase and monoamine oxidase enzymes, particularly for the treatment of two major neurodegenerative diseases, Alzheimer's Disease (AD) and Parkinson's disease (PD). Many compounds have been synthesized for this purpose, and some of them have been shown to display activities comparable or superior to the activities of current drugs used for the treatment of AD and PD. Within the concept of this review study, we have aimed to present the current drugs used for the treatment of AD and PD, their mechanism of action, the discussion behind the theory of designing dual inhibitor agents, and the presentation of the most active compounds with diverse heterocyclic scaffolds displayed in research studies published in the recent period.
Keywords: Alzheimer's disease; Parkinson's disease; Dual inhibitors; Monoamine oxidase; Cholinesterase; Heterocyclic scaffolds